Texture analysis as a method for grape berry characterization - Toth, Adrienn Mária; Veres, Szilvia; Zsofi, Zsolt (Acta Agraria Debreceniensis, 2022)
The marketability of table grapes is mainly characterized by berry size, color, taste and texture. Mechanical measurements of table grape berries could provide objective information on the textural qualities of grape berries. In addition, this method might be suitable to study the effects of phytotechnical methods (such as girdling) on table grape quality. The aim of this preliminary work was to demonstrate how instrumental testing could be used to examine the effects of girdling on berry grape texture and define the textural characteristics of table grape berries. Cane girdling was carried out at veraison in two table grape varieties. Texture analysis was performed several times during the maturity. Besides this examination another five varieties were analyzed to assess their berry mechanical properties. Double compression test was used to determine berry hardness and its derived parameters. Puncture test was applied to evaluate skin hardness, skin elasticity and skin break energy. Skin thickness was also investigated. Berry hardness, skin hardness and skin thickness of the girdled grapevines were significantly affected by this technique. Most of the textural parameters showed differences among the seven cultivars.